2002
DOI: 10.1007/s00276-001-0371-9
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive anatomy of the femoral portion of the iliopsoas muscle. Anatomical basis of anterior snapping of the hip

Abstract: Anterior hip snapping is a rare clinical observation. The physiopathological hypothesis currently held is a sudden slip of the iliopsoas tendon over the iliopectineal eminence. For symptomatic cases, a surgical technique is proposed. The aim of this work is to describe the anatomy of the femoral portion of the iliopsoas, which is the target of surgery. We have studied, through dissection of embalmed cadavers, the different components of the musculotendinous complex forming the femoral portion of the muscle and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
88
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(94 citation statements)
references
References 10 publications
1
88
0
5
Order By: Relevance
“…These include the (1) psoas major tendon, (2) medial fibers of the iliacus, which reliably merge with the psoas major tendon, (3) inferior fibers of the iliacus, which also join the main iliopsoas tendon before insertion, (4) lateral fibers of the iliacus, and (5) ilio-infratrochanteric muscular bundle, which together with the lateral fibers attach to the lesser trochanter without tendinous processes. Also, two hips showed complete splitting or a bifid psoas major tendon, which appeared physiologic [20]. Additionally, a recent dynamic sonographic study of 42 hips of healthy volunteers aiming to observe the five components, as described by Tatu et al [20], also reported one hip with a double or bifid psoas major portion of the iliopsoas tendon [7].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These include the (1) psoas major tendon, (2) medial fibers of the iliacus, which reliably merge with the psoas major tendon, (3) inferior fibers of the iliacus, which also join the main iliopsoas tendon before insertion, (4) lateral fibers of the iliacus, and (5) ilio-infratrochanteric muscular bundle, which together with the lateral fibers attach to the lesser trochanter without tendinous processes. Also, two hips showed complete splitting or a bifid psoas major tendon, which appeared physiologic [20]. Additionally, a recent dynamic sonographic study of 42 hips of healthy volunteers aiming to observe the five components, as described by Tatu et al [20], also reported one hip with a double or bifid psoas major portion of the iliopsoas tendon [7].…”
Section: Discussionmentioning
confidence: 99%
“…Bifid iliopsoas tendon as a possible cause of snapping hip has been reported in one dynamic sonographic study [4]. Anatomic variation suggestive of bifid iliopsoas tendon also has been described [14,20]. We report of a rare complication of arthroscopic release of internal snapping hip attributable to a missed bifid iliopsoas tendon.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…These two muscles merge to form one muscle: the iliopsoas muscle, which has a musculotendinous insertion on the lesser trochanter, though some muscle fibres of the iliacus attach directly on the lesser trochanter and proximal femur [29,30]. The anatomical and functional relationship between the iliopsoas muscle and the hip has been highlighted in previous studies.…”
Section: Iliopsoas Impingement Anatomical Considerationsmentioning
confidence: 99%